Knowledge And Attitude Of Pregnant Women About Malaria With Behavior To Seek Malaria Treatment - Pasnel Parna Wemy Gultom; Jenie Palupi; Yuniasih Purwaningrum; Syiska Atik Maryanti (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Belakang: Papua merupakan daerah endemik malaria dengan tingginya kasus malaria pada anak balita dan ibu hamil. Namun, kurangnya sosialisasi dan minat mencari tahu tentang malaria dan cara pengobatannya membuat penyakit malaria masih dianggap sebagai penyakit yang biasa oleh masyarakat di wilayah endemis malaria. Kasus malaria secara global mencapai 219 juta pada tahun 2017, dengan 435.000 kasus dikaitkan dengan malaria, di Indonesia, Profil Kesehatan Kabupaten Sarmi tahun 2017, 31.068 kasus pasien malaria. Kabupaten Sarmi kasus ibu hamil yang terinfeksi Malaria pada tahun 2010 sebanyak 260 orang (1,5% ) dengan jumlah penduduk 41.515 jiwa.Tujuan: Studi ini dilakukan untuk mengetahui hubungan pengetahuan dan sikap tentang malaria dengan perilaku ibu hamil untuk mencari pengobatan malaria dalam kehamilan di Puskesmas Samanente Kabupaten Sarmi.Metode: yang digunakan dalam penelitian ini yaitu metode analitik korelasional dengan pendekatan desain penelitian cross-sectional dengan menggunakan teknik simple random sampling sebanyak 30 orang. Instrumen penelitian yang digunakan yaitu menggunakan kuesioner. population in this study 30 people, this research used sampling technique Total Sampling with sampling 30 people. Inclusion criteria on this research is Willing to be a respondent, Mothers who are pregnant and currently or have suffered from malaria, Can read and write. Criteria exclusions in this study are Pregnant women who are sick at the time of the study, Pregnant women with Auto Immune, Pregnant women with pregnancy complicationsHasil: didapatkan responden dengan pengetahuan sedang yang tidak memiliki kebiasaan berobat malaria pada kehamilan adalah 56,3% dan kelompok responden dengan pengetahuan baik yang tidak memiliki kebiasaan berobat malaria pada kehamilan adalah 71,4%. Hal ini menunjukkan bahwa semakin tinggi tingkat informasi dapat meningkatkan proporsi perilaku tidak mencari pengobatan malaria selama kehamilan yaitu sebesar 15,1%. Hasil analisis menunjukkan bahwa tidak ada hubungan antara tingkat pengetahuan dan perilaku ibu hamil dalam mencari pengobatan malaria (P > 0.05). Ada hubungan antara sikap ibu hamil tentang malaria dan perilaku ibu hamil dalam mencari pengobatan malaria (P < 0.05). Kesimpulan: Meningkatnya pengetahuan dapat meningkatkan kesadaran ibu tentang penyakit malaria dan sikap yang baik dapat meningkatkan kewaspadaan terhadap penyakit malaria.Saran: menganjurkan ibu hamil untuk rutin melakukan kunjungan kehamilannya di Puskesmas agar dapat meningkatkan pengetahuan dan sikap tentang malaria dengan perilaku mencari pengobatan malaria dalam kehamilan. Kata Kunci : Malaria dalam kehamilan Pengetahuan, Pengobatan malaria sikap dan perilaku, ABSTRACT Background: Papua is a malaria endemic area with high malaria cases among children under five years and pregnant women. However, the lack of socialization and interest in finding out about malaria and how to medicate it makes malaria still considered a common disease by the people in malaria endemic areas. Malaria cases globally reached 219 million in 2017, with 435,000 cases attributed to malaria, in Indonesia, the Sarmi District Health Profile in 2017, 31,068 cases of malaria patients.Sarmi Regency cases of pregnant women infected with Malaria in 2010 were 260 people (1.5%) with a total population of 41,515 residents.Method: To ascertain the association between knowledge and attitudes about malaria and the behavior of pregnant women to seek treatment for malaria in pregnancy at Samanente Public Health Center, Sarmi Regency, a cross-sectional, correlational analysis study was carried out. The instrument was a questionnaire, with a sample size of 30 respondents, obtained using a simple random sampling method. population in this study 30 people, this research used sampling technique Total Sampling with sampling 30 people. Inclusion criteria on this research is Willing to be a respondent, Mothers who are pregnant and currently or have suffered from malaria, Can read and write. Criteria exclusions in this study are Pregnant women who are sick at the time of the study, Pregnant women with Auto Immune, Pregnant women with pregnancy complicationsResults: it was found that respondents with moderate knowledge who did not have the habit of seeking malaria treatment in pregnancy were 56.3% and the group of respondents with good knowledge who did not have the habit of seeking malaria treatment in pregnancy was 71.4%. This indicates that having a greater degree of information can improve the proportion of behavior for not seeking malaria treatment during pregnancy, which is 15.1%. The study found no correlation between pregnant women's knowledge level and behavior in seeking treatment for malaria (P>0.05). On the contrary, there was a significant correlation between pregnant women's attitudes toward malaria and their behavior in seeking malaria treatment (P<0.05).Conclusion: Improved knowledge is associated with increased maternal awareness of malaria, and positive attitudes can help raise awareness of malaria. It is to be expected that pregnant women who seek treatment for malaria will have a greater understanding of the disease and a more positive attitude toward it.Suggestion: We propose that pregnant women should be required to regularly visit the health center for prenatal care examinations in order to enhance their understanding and attitudes toward malaria by obtaining malaria medication during pregnancy. Keywords : Malaria in pregnancy, Malaria treatment, Knowledge, attitude and behavior